PROSES TEKNOLOGI PENDIDIKAN DAN PENERAPANNYA PADA PENDIDIKAN AGAMA ISLAM DI SMP NEGERI 3 MURUNG PUDAK KABUPATEN TABALONG PROVINSI KALIMANTAN SELATAN - Erihadiana, Mohamad; Rahman, Faisal (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2021)
THE PROCESS OF EDUCATIONAL TECHNOLOGY AND ITS APPLICATION IN ISLAMIC RELIGIOUS EDUCATION AT SMP NEGERI 3 MURUNG PUDAK, TABALONG REGENCY,  SOUTH KALIMANTAN PROVINCEThe purpose of this study is to describe correctly and realistically the process of educational technology and the application of using the WhatsApp application for Islamic religious educators at SMP Negeri 3 Murung Pudak, Tabalong Regency, South Kalimantan Province. The method used in this study is a qualitative descriptive method. The data from this study were obtained through interviews with PAI educators who became the main source of this research, then interviews with homeroom teachers, principals, school committees and 15 students. Observations in the form of passive participation observations and documentation as supporting data from the results of interviews. Educational technology is an urgent need during the Covid-19 pandemic. PAI educators at SMP Negeri 3 Murung Pudak try to learn and understand the use of social media in learning, such as showing pictures, films, recorders and others. The results are felt to be useful for PAI educators and students by using the advantages of social media, one of which is WhatsApp as a form of communicative interaction without protocol restrictions in the learning process.